Opening Magnetic Hysteresis by Axial Ferromagnetic Coupling: From Mono‐Decker to Double‐Decker Metallacrown. (20th January 2021) - Wang, Jin; Li, Quan‐Wen; Wu, Si‐Guo; Chen, Yan‐Cong; Wan, Rui‐Chen; Huang, Guo‐Zhang; Liu, Yang; Liu, Jun‐Liang; Reta, Daniel; Giansiracusa, Marcus J.; Wang, Zhen‐Xing; Chilton, Nicholas F.; et al.
Abstract: Combining Ising‐type magnetic anisotropy with collinear magnetic interactions in single‐molecule magnets (SMMs) is a significant synthetic challenge. Herein we report a Dy[15‐MCCu ‐5] (1‐Dy ) SMM, where a Dy III ion is held in a central pseudo‐ D 5 h pocket of a rigid and planar Cu5 metallacrown (MC). Linking two Dy[15‐MCCu ‐5] units with a single hydroxide bridge yields the double‐decker Dy[15‐MCCu ‐5]2 (2‐Dy ) SMM where the anisotropy axes of the two Dy III ions are nearly collinear, resulting in magnetic relaxation times for 2‐Dy that are approximately 200 000 times slower at 2 K than for 1‐Dy in zero external field. Whereas 1‐Dy and the Y III ‐diluted Dy@2‐Y analogue do not show remanence in magnetic hysteresis experiments, the hysteresis data for 2‐Dy remain open up to 6 K without a sudden drop at zero field. In conjunction with theoretical calculations, these results demonstrate that the axial ferromagnetic Dy–Dy coupling suppresses fast quantum tunneling of magnetization (QTM). The relaxation profiles of both complexes curiously exhibit three distinct exponential regimes, and hold the largest effective energy barriers for any reported d–f SMMs up to 625 cm −1 . Abstract : The magnetic hysteresis of a metallacrown magnet opens after introducing axial ferromagnetic by linking two mono‐decker Dy[15‐MCCu ‐5] units with a single hydroxide bridge to give the double‐decker Dy[15‐MCCu ‐5]2 single‐molecule magnet in which the anisotropy axes of the two Dy III ions are nearly collinear and the magnetic relaxation times are approximately 200 000 times slower than for the mono‐decker unit.